Relationship patterns in social networks of patients with depression in physical and online interactions: a sequential qualitative approach - Mayer, Gwendolyn; Selic, Maximilian; Schultz, Jobst-Hendrik (BMJ open, 2025)
Objectives First, to understand social needs in different mental disorders. Second, to determine patterns of social behaviour for either physical and online encounters in patients with depression. - Design Sequential qualitative design: (1) exploratory qualitative interview study investigating social needs of mentally disordered patients, followed by (2) qualitative network analysis of patients and healthy controls, analysed using inductive coding and triangulation for data aggregation and network visualisation. Standards for Reporting Qualitative Research (SRQR) were followed. - Setting (1) Professionals from inpatient and outpatient mental health services of psychosomatic medicine, psychotherapy and psychiatry. (2) Patients from outpatient services, healthy controls from various settings. - Participants (1) Nine mental health professionals with seven physicians and two psychological psychotherapists took part in interviews. (2) Network interviews were conducted with 10 patients with a diagnosis of depression given within the past year and nine healthy controls with matching sociodemographic characteristics. - Results Social relationships influence both the illness history and symptom profile of patients with depression. Patients reported less encounters compared with controls, although the frequency of their encounters was higher. Patients reported positive and trustful, yet more ambivalent relationships. Patients perceived less trust, but more influence on personal well-being by their encounters. Online contacts were described as more superficial by both groups. - Conclusions Qualitative network analysis reveals patterns of social needs in physical and online encounters and their visualisation allows for direct group comparisons. Biopsychosocial research designs with a larger sample size are recommended. Targeted interventions have to regard the complexity of relationship patterns in physical and online interactions.
Gesehen am 09.01.2026